The millard reaction in food processing, human nutrition and physiology - Finot, P. A.; International Union of Food Science and Technology; International Symposium on the Maillard Reaction (4th : 1989 : Lausanne, Switzerland) (Basel : Birkhauser Verlag, 1990)
42